Work Motivation Antecedents: the Effect of Human Resources Development in Improving Employee Performance - Sumarjo, Wahid; Setyowati, Ani; Haerofiatna, Haerofiatna; Haryadi, Didit; Rozi, Achmad (Universitas Pamulang, 2023)
Employee performance can be used as a benchmark for an agency in managing its human resources. This study, among others, examines and analyzes the factors in improving employee performance by developing human resources through work motivation. This research was conducted at the public works and spatial planning services with a population of 198 using a sample of 150 respondents. The questionnaire method was distributed using an interval scale of 1 strongly disagree to 10 strongly agree—data analysis technique using SEM PLS 4. The results of this study indicate that there is an influence of human resource development on employee performance, there is an influence of human resource development on work motivation, there is an influence of work motivation on employee performance, and work motivation can be a mediation in improving employee performance.